2017
DOI: 10.1186/s12936-017-2142-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-malarial interaction and gametocytocidal activity of cryptolepine

Abstract: BackgroundDiscovery of novel gametocytocidal molecules is a major pharmacological strategy in the elimination and eradication of malaria. The high patronage of the aqueous root extract of the popular West African anti-malarial plant Cryptolepis sanguinolenta (Periplocaceae) in traditional and hospital settings in Ghana has directed this study investigating the gametocytocidal activity of the plant and its major alkaloid, cryptolepine. This study also investigates the anti-malarial interaction of cryptolepine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…First, the cells (2 × 10 7 cells/ml) were incubated in PBS supplemented or not with 5 mM glucose, and each of these samples was treated or not treated with 16 mM DCA. The functionality of the mitochondrial dehydrogenases (usually considered a reliable indicator of mitochondrial viability) was evaluated by assessing the irreversible reduction of resazurin (7-hydroxy-3H-phenoxazine-3-one 10-oxide; Sigma) to resorufin (7-hydroxy-3H-phenoxazin-3-one), a red-ox fluorimetric indicator, used in viability assays for trypanosomatids and apicomplexans ( 81 85 ). Parasite samples (2 × 10 6 cells/ml) from each one of the four groups described above were aliquoted in 96-well plates (100 μl per well) and incubated in the presence of 0.125 μg/μl resazurin for 3 h (in the absence of light) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…First, the cells (2 × 10 7 cells/ml) were incubated in PBS supplemented or not with 5 mM glucose, and each of these samples was treated or not treated with 16 mM DCA. The functionality of the mitochondrial dehydrogenases (usually considered a reliable indicator of mitochondrial viability) was evaluated by assessing the irreversible reduction of resazurin (7-hydroxy-3H-phenoxazine-3-one 10-oxide; Sigma) to resorufin (7-hydroxy-3H-phenoxazin-3-one), a red-ox fluorimetric indicator, used in viability assays for trypanosomatids and apicomplexans ( 81 85 ). Parasite samples (2 × 10 6 cells/ml) from each one of the four groups described above were aliquoted in 96-well plates (100 μl per well) and incubated in the presence of 0.125 μg/μl resazurin for 3 h (in the absence of light) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Cryptolepis sanguinolenta is a plant indigenous to Africa where it has been used in traditional medicine to treat malaria, tuberculosis, hepatitis, and septicemia (45). Cryptolepis sanguinolenta has been shown in preclinical studies to have antiinflammatory (46,47) antibacterial (48)(49)(50), anti-fungal (51), anti-amoebic (52), and anti-malarial (53,54) properties. Two preliminary clinical studies have documented significant efficacy in treating uncomplicated malaria without signs of overt toxicity (55).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptolepis sanguinolenta is a plant indigenous to Africa where it has been used in traditional medicine to treat malaria, TB, hepatitis, and septicemia (51). In addition to the various uses documented in ethnomedicine, Cryptolepis sanguinolenta has been shown in preclinical studies to have anti-inflammatory (52, 53) antibacterial (5459), Anti-fungal (55, 60), anti-amoebic (61) and anti-malarial (6265) properties. Two preliminary clinical studies have shown Cryptolepis to have significant efficacy in treating uncomplicated malaria without signs of overt toxicity (66, 67).…”
Section: Discussionmentioning
confidence: 99%